Beyond the Victim: A Quantitative Analysis of Ethical Leadership and Individual Ideology as Antecedents of Workplace Mobbing in Poland - Dobrowolska, Malgorzata; Izydorczyk, Bernadetta (European Journal of Social Science Education and Research, 2025)
Research on workplace mobbing has extensively documented its severe mental health consequences, often focusing on the victim’s experience. This study shifts the analytical lens from consequences to antecedents, aiming to prevent mobbing by understanding its origins. It quantitatively examines the predictive power of both organizational factors (perceived ethical leadership) and individual-level factors (employee’s ethical ideology, specifically idealism and relativism) on the experience of mobbing behaviors in the Polish workplace. A cross-sectional survey design was employed, collecting data from 512 full-time employees in large organizations in Poland. The survey utilized established psychometric scales: the Negative Acts Questionnaire-Revised (NAQ-R) for mobbing, the Ethical Leadership Scale (ELS), and the Ethics Position Questionnaire (EPQ) for ideology. Data were analyzed using hierarchical multiple linear regression to test the unique contribution of organizational and individual predictors. Results indicate that ethical leadership is the single most powerful deterrent, showing a robust negative relationship with perceived mobbing (β = -.412, p < .001). Individual ethical ideology was also a significant predictor; idealism negatively predicted mobbing experiences (β = -.179, p < .01), whereas relativism was a significant positive predictor (β = .204, p < .001). The complete model explained 28.7% of the variance in perceived mobbing. This study provides one of the first empirical models in an Eastern European context to simultaneously assess the influence of leadership and individual ideology on mobbing. The findings offer actionable, preventative insights, demonstrating that while an individual’s ethical framework is relevant, the cultivation of ethical leadership is the most critical organizational defense against workplace toxicity.